Penentuan Karyawan Produksi Voucher Pada PT . XYZ Dengan Metode WLA dan Stopwatch - Diah Andrianingsari; Dimas Saputra; Adhi Dharna Suriyanto; Miwan Kurniawan Hidayat; Bayu Nur Kuncoro (LPPM Universitas Bina Sarana Informatika, 2026)
PT.XYZ is a company engaged in the fields of technology, media, and information, specifically in the form of digital vouchers. The products created are in the form of digital voucher products. PT. PT.XYZ has several departments, one of which is the voucher production department. In that department, there are issues such as the suboptimal determination of labor, workload levels, and work time calculations in producing vouchers. To find a solution to the problem, calculations were performed using the workload analysis (WLA) method and Stopwatch. Based on the calculations from both methods, it was found that the WLA method indicated an excess of 5 workers, while the Stopwatch method indicated an excess of 2 workers. For the calculation of the workload level (FTE), a result of 0.761 was obtained, which is classified as underload (insufficient workload) because the FTE value is <1. For the working time in the production of digital vouchers in the production unit, a result of 23,639 seconds (6.5 hours) was obtained. After determining that the workload level in the production unit is classified as underload and based on the labor calculations using the WLA and Stopwatch methods indicating an excess of labor, the solution to the problem is that PT.XYZ is advised to reduce the workforce to optimize the workload level, increase production levels, and reduce company costs